Business intelligence and the cloud : strategic implementation guide - Gendron, Michael S., 1957- (Wiley, 2014)
How to measure cloud computing options and benefits to impact business intelligence infrastructure This book is a guide for managers and others involved in using cloud computing to create business value. It starts with a discussion of the media hype around cloud computing and attempt to pull together what industry experts are saying in order to create a unified definition. Once this foundation is created-assisting the reader's understanding of what cloud computing is-the discussion moves to getting business benefits from cloud computing. Lastly, the discussion focuses on examples of cloud computing, public clouds, private clouds, and virtualization.